IMPLEMENTASI PENDEKATAN TARI PENDIDIKAN DALAM PEMBELAJARAN TARI DI TK KESUMA BANDAR LAMPUNG - Diva Arum Kinanti; Dwiyana Habsary; Nabilla Kurnia Adzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the educational dance approach in dance learning at Kesuma Kindergarten, Bandar Lampung. This study uses a qualitative method with a descriptive approach. The research subjects include educators and students of the Matahari class, while the research object is focused on the dance learning process that applies the educational dance approach. Data collection techniques are carried out through observation, documentation and interviews. Data validity is obtained through triangulation of sources and techniques, while data analysis is carried out through the stages of data reduction, data presentation, and finally the conclusion drawing stage. The results of the study indicate that the implementation of the educational dance approach in dance learning is carried out through two elements of educational dance, namely, creative dance and expressive dance. The creative dance stage is able to provide space for students to explore movements in forming animals freely, while the expressive dance stage is able to provide space for students to express feelings and emotions through question instructions and broad hand movements. The implementation of learning helps foster students' self-confidence in exploring the forms of aquatic animals, creating a pleasant learning atmosphere, and increasing students' learning readiness so that students become more focused. Overall, the implementation of an educational dance approach can create a fun learning environment and encourage students to be more creative and expressive.